Analysing the Relationship between Entrepreneurship Education, Self-Efficacy, and Entrepreneurial Performance - Itot Bian Raharjo; Abu Muna Almaududi Ausat; Andriya Risdwiyanto; Sivy Sondari Gadzali; Hizbul Khootimah Azzaakiyyah (Departement of Mathematics Education, 2023)
Entrepreneurship education has been proven to improve knowledge, competencies, attitudes, and most importantly, self-efficacy. An entrepreneur's self-efficacy is allegedly able to create superior entrepreneurial performance. This study is designed to examine the relationship between entrepreneurship education in terms of entrepreneurial self-efficacy and entrepreneurial performance. This research is qualitative in nature. Data analysis entails listening to and documenting relevant information, then summarizing and drawing conclusions based on the results. The relationship between entrepreneurship education and self-efficacy is interrelated. These two dimensions are important capital in creating good entrepreneurial performance, which is certainly the performance expected by many parties, especially those who do it. Entrepreneurship education is indeed a knowledge base that individuals must have before stepping into a real entrepreneurial career. Without business knowledge, individuals will be overwhelmed when faced with various business problems as entrepreneurs. It is hoped that the findings of this research will serve as a point of reference for future conversations on related subjects. In addition, it can be a formal discussion material in higher education, especially entrepreneurship, management, and business administration study programmes.